Impactos financeiros dos critérios de aceitação na medição fiscal de gás natural - SANTOS, Raimar Barbosa (2017)
The oil industry is essential to the world economy. In Brazil, Natural Gas (NG) represents an important source of financial resources for the Union, through the collection of revenues paid by companies that exploit this natural and nonrenewable resource, and the distribution of government participation. Therefore, it is of the utmost importance that the volumes of NG produced and marketed, for the purposes of tax calculations, have the maximum reliability in their results. Thus, in order to contribute to increase the reliability of natural gas tax measurements, this dissertation aims to evaluate the financial impact of the accuracy of acceptance criteria in orifice plate flow measurement. The motivation for the development of the research originates in the advance of the knowledge about measurement of natural gas, subject little discussed. And, also, by the contribution of improvements to the tax measurement process of natural gas. The work was developed from simulations, as well as the determination of flow rates up to the limits of the established calibration acceptance criteria of each variable using DIGIOPC software. After calculating the flow values, considering all the possibilities, the flow deviations were calculated, as well as the previous financial deviations of the analyzed criteria. The methodology adopted was based on bibliographic review, normative and data collection in the field. The bibliographic and normative research provided all theoretical basis on the subject and the field research contributed to collect all the necessary data for scientific simulation, analysis and conclusion. The results of the research included an estimate of the financial impact on the revenue of the companies that produce NG in range of 9,369,249.50 R$ / month to 10,339,406.89 R$ / month, and concomitantly in the distribution of royalties between R$ 871,340.20 and R $ 961,564.84 / month. At the state level, the financial impact on ICMS tax revenue resulting from the movement of NG in the State of Bahia ranged from 83,017.18 R $ / month to 92,371.22 R$ / month. In conclusion, the paper suggests that the acceptance criteria currently used are reevaluated and standardized.